2017
DOI: 10.1007/s13201-017-0604-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of biochar and chitosan blend for heavy metals uptake from synthetic and industrial wastewater

Abstract: Heavy metals are usually released into water bodies from industrial/domestic effluents such as metal plating industries, mining and tanneries. Adsorption is a fundamental process in the physiochemical treatment of wastewaters because of its low cost. Great efforts have been made to use the economically efficient and unconventional adsorbents to adsorb heavy metals from aqueous solutions, such as plant wastes and agricultural waste. Biochar mixed with chitosan after crosslinking can be casted into membranes, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(11 citation statements)
references
References 7 publications
(6 reference statements)
1
7
0
Order By: Relevance
“…They can be used as high quality adsorbents for sewage treatment [28]. Scholars at home and abroad have found that biomass materials have strong adsorption capacity for heavy metal ions, methylene blue and so on, and the adsorption effect is better after modification [29][30][31]. Chen Yimin et al used solid waste produced by a freeze-dried fruit and vegetable production enterprise to treat wastewater containing hexavalent chromium ion, copper ion and methylene blue.…”
Section: Adsorption Capacity Utilization Methodsmentioning
confidence: 99%
“…They can be used as high quality adsorbents for sewage treatment [28]. Scholars at home and abroad have found that biomass materials have strong adsorption capacity for heavy metal ions, methylene blue and so on, and the adsorption effect is better after modification [29][30][31]. Chen Yimin et al used solid waste produced by a freeze-dried fruit and vegetable production enterprise to treat wastewater containing hexavalent chromium ion, copper ion and methylene blue.…”
Section: Adsorption Capacity Utilization Methodsmentioning
confidence: 99%
“…Major pollutants involved here are acrolein, amines, mercaptans, dibutyl sulfide, hydrogen sulfide, phenolics compounds, ammonia, mercury, cyanide ,and so on [3] A biochar in combination with chitosan after cross linking can be introduced into membranes, beads and solution used as an effective adsorbent for heavy metals like copper, lead, arsenic, cadmium ,and many other heavy metals. [4] . Gliricidia biochar is material for crystal violet removal based on pH value, contact time and dosage.…”
Section: Introductionmentioning
confidence: 99%
“…Once desorbed, heavy metals will migrate to farther places and cause large-scale pollution. So many scholars have analyzed and studied the phenomenon that 'colloid promotion' can accelerate the migration of pollutants (especially organic pollutants and heavy metals) in water or soil [7]. So far, among the main methods for removing and recovering heavy metals in water (chemical precipitation, redox, ion exchange, biological filtration, activated sludge method and adsorption), the adsorption method has the advantages of good purification effect, simple operation, and no secondary pollution.…”
Section: Introductionmentioning
confidence: 99%